Antioxidant and Chelating Activity of Nontoxic Jatropha curcas L. Protein Hydrolysates Produced by In Vitro Digestion Using Pepsin and Pancreatin - Santiago Gallegos Tintoré; Cristina Torres Fuentes; Javier Solorza Feria; Manuel Alaiz; Julio Girón Calle; Alma Leticia Martínez Ayala; Luis Chel Guerrero; Javier Vioque (Journal of Chemistry)
The antioxidant and metal chelating activities in J. curcas protein hydrolysates have been determined. The hydrolysates were produced by treatment of a nontoxic genotype with the digestive enzymes pepsin and pancreatin and then were characterized by fast protein liquid chromatography and reverse phase chromatography. Peptidic fractions with higher radical scavenging activity were analysed by matrix-assisted laser desorption/ionization mass spectrometry. The antioxidant activity was determined by measuring inhibition of the oxidative degradation of β-carotene and by measuring the reactive oxygen species (ROS) in Caco-2 cell cultures. Cu2+ and Fe2+ chelating activities were also determined. The hydrolysates inhibited the degradation of β-carotene and the formation of ROS in Caco-2 cells. The lower molecular weight peptidic fractions from FPLC had stronger antioxidant activity in cell cultures compared with the hydrolysates, which correlated with a higher content in antioxidant and chelating amino acids. These fractions were characterized by a large presence of peptides with different molecular masses. The hydrolysates exhibited both Cu2+ and Fe2+ chelating activity. It was concluded that J. curcas is a good source of antioxidant and metal chelating peptides, which may have a positive impact on the economic value of this crop, as a potential source of food functional components.